2006
DOI: 10.1021/ja0584626
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Study of the Magnetic Properties and Electronic Structure of the Hydroxide Complex of Substrate-bound Heme Oxygenase from Neisseria Meningitidis:  Influence of the Axial Water Deprotonation on the Distal H-bond Network

Abstract: The substrate and active site residues of the low-spin hydroxide complex of the protohemin complex Neisseria meningitidis heme oxygenase, HO, NmHO, have been assigned by saturation transfer between the hydroxide and previously characterized aquo complex. The available dipolar shifts allowed the quantitation of both the orientation and anisotropy of the paramagnetic susceptibility tensor. The resulting positive sign, and reduced magnitude of the axial anisotropy relative to the cyanide complex, dictate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 61 publications
(241 reference statements)
5
30
0
Order By: Relevance
“…The 1 H-NMR spectra obtained for IsdIFe 3þ at pH 6, 7, and 8.2 ( Fig. 2A) indicate that the interconversion of coordinated water and coordinated hydroxide is slow on the NMR time scale as previously reported for bovine myoglobin variants in which the distal His is replaced by Gln or Asn (43) and for two bacterial heme oxygenases (41,44).…”
Section: Discussionsupporting
confidence: 75%
“…The 1 H-NMR spectra obtained for IsdIFe 3þ at pH 6, 7, and 8.2 ( Fig. 2A) indicate that the interconversion of coordinated water and coordinated hydroxide is slow on the NMR time scale as previously reported for bovine myoglobin variants in which the distal His is replaced by Gln or Asn (43) and for two bacterial heme oxygenases (41,44).…”
Section: Discussionsupporting
confidence: 75%
“…Thus, it can be concluded that in the case of low-spin ferric peroxo/hydroperoxo hemes, the observed EPR spectra with small g spread and 56 The proposal by Rivera was mainly based on the detection of unusual 13 C NMR spectra of the hydroxide complex of HO from Pseudomonas aeroginosa reconstituted with 13 C labeled heme. 55 However, a recent proton NMR investigation of the ferric hydroxide complex of a homologous HO from Neisseria meningitidis has demonstrated unambiguously a d π ground state for the hydroxide complex.…”
Section: Discussion Electronic Structure Analysismentioning
confidence: 99%
“…The chemical shifts for several labile protons in this network exhibit strong low-field bias indicative of significant H-bonding. (23-27)…”
mentioning
confidence: 99%
“…On the one hand, δ dip directly monitors the H-bond properties of the ligated water molecule/hydroxide ion. (26, 27, 31, 33) For high-spin ferrihemoproteins, Δχ is large, negative, highly axial, (26, 31, 34-36) and arises overwhelmingly from the zero-field splitting constant, D, as given by: (32)…”
mentioning
confidence: 99%